Comparative Study of Daphne du Maurier’s Rebecca Film Adaptations. Chronotope of a “Castle” - Labuznaya, V.Yu (Художественная культура, 2021)
The article performs the comparative study of Daphne du Maurier’s Rebecca film adaptations. It investigates motion pictures by A. Hitchcock (1940), R. Milani (2008) and B. Wheatley (2020). The analysis of the narrative-discursive techniques used by these authors aims to consider the problem of screen representation of the Rebecca’s specific spacetime model. The main investigated subject is the screen image of Manderley estate, its impact on diegesis, plot and symbolism in these movies. Manderley as an aesthetic complex corresponds to the chronotope of the “castle” in the interpretation of M. Bakhtin. Accordingly, the comparative study of the operations performed with it reveals the most important characteristics and traits of this spacetime model and shows how it applies with the detective genre or plots with a detective component. The “castle” as a spacetime structure that outlines the external boundaries and sets the internal laws of diegesis; its role in the “mystery” logics and the development of detective intrigue; “castle” as a plot-forming principle and metacharacter — all these questions concerned in terms of screen arts.